Exploring the potential targets of the Abrus cantoniensis Hance in the treatment of hepatitis E based on network pharmacology - Xu, Ziheng; Wang, Can; Luan, Zuxiang; Zhang, Dapei; Dong, Baiqing (Frontiers in Veterinary Science, 2023)
Hepatitis E is a disease of public health significance caused by the cross-species transmission of zoonotic hepatitis E virus (HEV) infection. There are no specific drugs. In this study, network pharmacology was used to reveal the mechanism of treatment of the active constituents of the Abrus cantoniensis Hance on hepatitis E. Based on the previously published representative components of Abrus cantoniensis Hance, we were screened the active components with OB≥20% and DL≥0.1 in Abrus cantoniensis Hance based on the TCMSP, predicted the target online through Swiss target prediction, and integrated the hepatitis E target in the GeneCards and DisGenet databases. Then, the core target was screened and the GO and KEGG enrichment and the network of the drug-active-ingredient-disease-pathway-target analysis were performed by the Cytoscape software. There were 11,046 hepatitis E targets, including PI3K-AKt, SRC, MAPK, PTPN11, EGFR, STAT1 and so on. The core ingredients include Oleanolic acid, Butin, β-sitosterol, Soyasapogenol E, 5,7-dihydroxy-2-methyl-8-[(2S,3R,4S,5S,6R)-3,4,5-trihydroxy-6-(hydroxymethyl)oxan-2-yl]oxychromen-4-one, Stigmasterol, Emodin, Physcion, and Enoxolone. A total of 1,410 GO enrichment results of core targets, including 1,246 biological process, 51 cell composition and 113 molecular function results. KEGG pathway was enriched in 150 related pathways, suggesting that Abrus cantoniensis Hance acts on cancer signaling pathway, endocrine resistance pathway, PI3K-AKt signaling pathway, MAPK, TNF and other signaling pathway. Through key components such as Oleanolic acid, Butin, β-sitosterol, Stigmasterol, and Enoxolone and other components interferes with AKT1, IL-6 and TNF, and regulates pathway in cancer, PI3K-AKt signaling pathway and MAPK pathway to play a therapeutic role in hepatitis E.